The Role of Work-Life Balance and Skills Development on Sustainable Employee Engagement in Hospitals - Pemi Puji Apriani; Setyo Riyanto; Dewi Nusraningrum; Kasmir Kasmir (Universitas Mercu Buana, 2026)
This study systematically synthesizes empirical evidence on the roles of work–life balance (WLB) and skills development in shaping sustainable employee engagement in hospital settings, with particular attention to healthcare contexts in developing countries, especially Asia. A Systematic Literature Review (SLR) was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines as a reporting framework. Relevant studies were identified through comprehensive searches of major international databases, including Scopus, ScienceDirect, Springer, Wiley, Sage, IEEE, Web of Science, and Google Scholar. From an initial pool of 7,394 articles, a systematic screening and eligibility process resulted in 124 peer-reviewed empirical studies included in the final synthesis.The findings indicate that work–life balance is consistently associated with reduced stress and burnout, improved psychological well-being, and sustained employee engagement among healthcare workers. Skills development—particularly through training, upskilling, reskilling, and digital-based learning—emerges as a key mechanism for strengthening competence, motivation, and workforce adaptability. The review further reveals that studies simultaneously examining both variables remain limited, indicating a fragmented research landscape. Organizational factors such as leadership support, organizational culture, and digital readiness, together with individual resilience and intrinsic motivation, frequently moderate or mediate these relationships.Rather than estimating effect sizes, this SLR provides a conceptual synthesis that consolidates fragmented findings and highlights research gaps, including the dominance of cross-sectional designs and the need for more integrative and longitudinal studies. Practically, the results underscore the importance of aligning work–life balance initiatives with continuous skills development to foster sustainable employee engagement in healthcare organizations.